Systematic Review of Defibrillation Threshold Testing at De Novo Implantation. (April 2016) - Phan, Kevin; Ha, Hakeem; Kabunga, Peter; Kilborn, Michael J.; Toal, Edward; Sy, Raymond W.
Abstract : Background—: Recent results from the largest multicenter randomized trial (Shockless IMPLant Evaluation [SIMPLE]) on defibrillation threshold (DFT) testing suggest that while shock testing seems safe, it does not reduce the risk of failed shocks or prolong survival. A contemporary systematic review of DFT versus no-DFT testing at the time of implantable cardioverter–defibrillator implantation was performed to evaluate the current evidence and to assess the impact of the SIMPLE study. Methods and Results—: Electronic searches were performed using 6 databases from their inception to March 2014. Relevant studies investigating implant DFT were identified. Data were extracted and analyzed according to predefined clinical end points. Predefined outcomes for interrogation were all-cause mortality, composite end point of implantable cardioverter–defibrillator efficacy (arrhythmic deaths and ineffective shocks), and composite safety end point (the sum of complications recorded at 30 days). Meta-analysis was performed including 13 studies and 9740 patients. No significant differences between DFT versus no-DFT cohorts were found in terms of all-cause mortality (risk ratio, 0.90; 95% confidence interval, 0.71–1.15; P =0.41), composite efficacy outcome (risk ratio, 1.24; 95% confidence interval, 0.65–3.37; P =0.51), and 30-day postimplant complications (risk ratio, 1.18; 95% confidence interval, 0.87–1.60; P =0.29). No significant difference was found in the trends observed when the results of the SIMPLE study were excluded or included. Conclusions—: This systematic review of contemporary data suggests a modest average effect of DFT, if any, in terms of mortality, shock efficacy, or safety. Therefore, DFT testing should no longer be compulsory during de novo implantation. However, DFT testing may still be clinically relevant in specific patient populations. Abstract : Supplemental Digital Content is available in the text.